Charity Begins at Home: Doing Gender Inclusivity in Teacher Education - Mishra, Preeti Vivek (JOURNAL OF INDIAN EDUCATION, 2019)
The policy discourse in teacher education is replete with clarion calls to institutions and individuals, respectively, to prepare and become teachers who are ‘humane’ and ‘inclusive’. The present paper flips the reality on its head to investigate how inclusive are the conceptualisations which are driving the vision of a teacher in recent discourse on teacher education policy frameworks. Specifically, the paper seeks to focus on the construction of gender in National Curricular Framework for Teacher Education-2009 and gauge how much inclusive this construction is. The inquiry is premised on the assertion that any discussion on gender inclusivity in policy frameworks must firstly, examine how the policy discourse itself posits gender, and secondly, whether and how it recognises and addresses teacher embodiments. As the present inquiry is based on textual articulations in a finite form as encapsulated in NCFTE-2009, the methodology adopted is qualified as a discursive textual analysis. Findings reveal that NCFTE’s vision displays a recurrent commitment to the values enshrined in the Constitution of India and it is against this backdrop that the concept of inclusion is seemingly framed too. It is in its charting of the topography of social exclusion in education that NCFTE makes evident its recognition of and concern for inter alia gender-based exclusion. NCFTE displays a clear intent through curricular suggestions and policy rhetoric that teacher educators and teacher trainees alike need to engage with gender as both an area of study as well as of self-scrutiny. A closer scrutiny however, reveals a tendency to abridge the entire gender conundrum to mean girls only. A biological essentialist underpinning too is evident as the framework conflates sex with gender, and fails to recalibrate the discourse of gender.